The Protection of Women and Children Post-Divorce in Sharia Courts in Aceh: A Sociological Perspective - Kasim, Fajri M; Nurdin, Abidin; Muthalib, Salman Abdul; Syarifuddin, Samsinar; Samad, Munawwarah (AHKAM : Jurnal Ilmu Syariah, 2022)
This  study  discusses  the  protection  of  women  and  children  after divorce  at  the  Syar'iyah  Court  in  Aceh.  A  legal  sociology  approach  is  used to  draw  the  decisions  of  the  Banda  Aceh,  Aceh  Besar,  Pidie,  Bireuen,  and Lhokseumawe Syar'iyyah Courts. The interviews were conducted with judges, community  leaders,  village  heads,  heads  of  the  Office  of  Religious  Affairs (KUA),  academics,  traditional  figures,  and  non-governmental  organizations (NGO) activists. This study concludes that the Syar'iyah Court in Aceh, in its  decision,  has  ensured  the  rights  of  women  and  children.  The  Syar'iyah Court  in  Aceh  determined  the  provision  of  'iddah,  muṭ'ah  maintenance, joint  assets,  and  childcare  rights  to  women.  Children  get  living  expenses, guardianship from the family, and care from the mother. Sociologically, the law has functioned as a means of social control through the Syar'iyah Court and judges as the main part of the legal structure supported by other elements of society so that the protection of women and children can be realized fairly.Keywords: protection of women and children; divorce; legal sociology; sharia court AbstrakKajian  ini  membahas  perlindungan  perempuan  dan  anak  setelah perceraian pada Mahkamah Syar’iyah di Aceh. Dengan pendekatan sosiologi hukum,  studi  ini  bersumber  pada  putusan-putusan  Mahkamah  Syar’iyyah Banda Aceh, Aceh Besar, Pidie, Bireuen, and Lhokseumawe dan wawancara kepada hakim, tokoh masyarakat, kepala desa, kepala Kantor Urusan Agama (KUA),  akademisi,  tokoh  adat  dan  aktivis  Lembaga  Swadaya  Masyarakat (LSM). Kajian ini menyimpulkan bahwa Mahkamah Syar’iyah di Aceh dalam putusannya telah memastikan hak-hak perempuan dan anak. Mahkamah Syar’iyah di Aceh menetapkan pemberian nafkah ‘iddah, nafkah muṭ‘ah, harta bersama dan hak pengasuhan anak kepada perempuan; dan anak mendapatkan biaya hidup, perwalian dari keluarga dan pengasuhan dari ibu. Secara sosiologis, hukum telah berfungsi sebagai alat kontrol sosial melalui Mahkamah Syar’iyah dan  hakim  sebagai  bagian  utama  dari  struktur  hukum  yang  didukung  oleh elemen masyarakat lainnya sehingga perlindungan terhadap perempuan dan anak dapat terwujud secara adil.Kata Kunci: perlindungan perempuan dan anak; perceraian; sosiologi hukum; Mahkamah Syar’iyah